Cathodic Stripping Voltammetric Determination of Cerium Using Indium Tin Oxide (ITO). Issue 4 (16th January 2017) - Ojo, Kolade; Zhao, Daoli; Rusinek, Cory A.; Pixley, Sarah K.; Heineman, William R.
Abstract: Due to its numerous applications in the field of metallurgy and its role as an alloying element for slowing down the biodegradation of pure magnesium typically known to have very low corrosion resistance, the need to develop simple and inexpensive methods for determination of cerium is important. Ce 3+ was determined by cathodic stripping voltammetry (CSV) using Osteryoung square‐wave voltammetry (OSWV) for the stripping step. Indium tin oxide (ITO) was used as the working electrode because of its very good positive potential range with smooth background current. Under optimized conditions, the calibration plot was linear in the concentration range of 100 nM to 700 nM Ce 3+ . A calculated detection limit of 5.8 nM was found for a 5 min deposition time at ITO based on the 3σ method. Interference from selected metal ions was also examined, and no significant interferences were observed. The good selectivity of this sensor makes it a good candidate for practical applications such as monitoring Ce 3+ released into solution during the biodegradation of Mg−Ce alloys being developed for resorbable biomedical implants. Abstract :